Deep-sea coral reef ecology : feeding mechanisms, community interactions, and habitat associations of deep-sea echinoids - Stevenson, Angela (Trinity College (Dublin, Ireland). Department of Botany, 2014)
The ultimate aim of the thesis was to probe into the ecology of deep-sea echinoids in order to contribute newfound information to this topic, as well as develop tools to facilitate ecological work in deep-sea environments. This was achieved using a multifaceted approach, including analyses of gut content and stable isotope, as well as video and image analyses; data and samples for these came from field work in Ireland and France, in the NE Atlantic; and seamounts in Australia and New Zealand, in the SW Pacific.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin